Taxonomic and morphological revision of butterfly rays of the Gymnura micrura (Bloch & Schneider 1801) species complex, with the description of two new species (Myliobatiformes: Gymnuridae) - Yokota, Leandro; Carvalho, Marcelo Rodrigues De (Zootaxa, 2017)
An extensive taxonomic revision of Gymnura micrura based on external and internal morphology, and considering specimens from its entire geographical distribution in the Atlantic Ocean, is presented. Gymnura micrura is redescribed and a neotype is designated; its distributional range is limited to the Southwestern Atlantic. Two new species of butterfly rays are described: Gymnura lessae, sp. nov., occurring in the North and Central Western Atlantic, and Gymnura sereti, sp. nov., found in the Eastern Central Atlantic. The three species are morphologically very similar (with G. micrura most similar to G. lessae, sp. nov.) and cannot be distinguished based on the primary diagnostic characters typically utilized for butterfly rays. The dorsal color, smaller size and eventual presence of a dorsal fin in some males may be helpful to distinguish G. micrura, whereas the size and morphology of the clasper are the main external characters separating G. sereti, sp. nov., from the other two species, although the shape of disc (especially among adult males) and contour of the lower lip are also helpful. Despite the skeleton being conservative among the species, we found consistent variations that support the validity of the new species described. Due to similarity in external morphology these internal characters were fundamental to discriminate the new species. The scapulocoracoid was an important diagnostic skeletal structure, exhibiting a series of variations that separated the three species. Variations in the synarcual, outline of the dorsal cranial fontanelle, number and shape of mesopterygia, and small differences in the mandibular arches and pelvic girdle were useful to diagnose G. sereti, sp. nov. The contour of the hyomandibula was an important diagnostic character distinguishing G. lessae, sp. nov., from the other two species. Meristic data were also useful, with G. sereti, sp. nov., presenting a lower number of radials in the second element of the mesopterygium and a higher number of diplospondylous vertebrae. In contrast, G. lessae, sp. nov., presented a higher number of pectoral-fin radials. Subtle, but consistent differences, were also found in the design of the ventral lateral-line system. A Canonical Discriminant Analysis provides strong statistical support for the validity of the new species, significantly distinguishing the three species groupings (p < 0.00001). External morphology, ventral lateral-line system and skeleton are described and illustrated for all three valid species.